Spectrophotometric Evaluation of Natural Tooth Color Distribution Across Three Dental Shade Guide Systems - Julija Zarkova Atanasova; Katerina Zlatanovska; Ljubica Proseva Pelivanova; Sandra Atanasova; Bruno Nikolovski; Natasha Longurova; Pavle Apostoloski (European Scientific Journal, ESJ, 2026)
Accurate determination of tooth color is fundamental to achieving optimal outcomes in restorative dentistry. Spectrophotometry has emerged as an objective method for color assessment, overcoming the limitations of visual shade selection. This study aimed to evaluate the distribution of natural tooth color using spectrophotometric measurements, to compare its representation across three dental shade guide systems, and to assess its variation according to sex and age. A total of 235 participants aged 18–69 years were included in this cross-sectional study. The shade of the maxillary central incisors was measured using a non-contact spectrophotometer (ShadePilot). The obtained values were matched to the VITA Classical, Ivoclar Chromascop, and VITA 3D-Master shade guides. Significant differences in shade distribution were observed across all three systems. Statistical analysis was performed using the Pearson Chi-square test (p < 0.05). Shades from Group A (VITA Classical), Group 100 (Chromascop), and Group 2 (VITA 3D-Master) were the most prevalent, with A2 (29.79%), 120 (25.53%), and 2M2 (15.74%) being the most frequently recorded shades, respectively. Both sex and age showed a statistically significant influence on tooth color (p < 0.05), with a clear trend toward darker shades in older age groups and among males. Natural tooth color distribution varies depending on the shade guide system used and is significantly influenced by demographic factors. Spectrophotometric analysis offers an objective method for shade determination, facilitating more accurate color matching and improved esthetic outcomes in clinical practice.